Pengedukasian Kesehatan Reproduksi dan Pencegahan Kejahatan Seksual Online dalam Upaya Sekolah Membentuk Karakter Remaja Bertanggungjawab - Ahmad, Deni Nasir (JPM (Jurnal Pemberdayaan Masyarakat), 2018)
The purpose of this extension activity is so that students gain knowledge about their reproductive health and how to use social media online wisely. This activity is carried out so that students in this case the age of adolescents approaching adults gain knowledge and the foundation of the character of responsibility to themselves so that teenagers can fortify themselves through knowledge that has been given thoroughly and build self-confidence through character building material for students. In carrying out the community service activities, the servant performs an approach or method of dedication in the form of counseling with material exposure activities, giving questionnaires and interactive discussions between devotees and students. From the results of community service activities that have been carried out, it can be concluded that the service participants obtain new knowledge about reproductive health and efforts to prevent sexual violence on social media online and for servants to gain new knowledge and experience on how to approach character education after adolescence in the age of globalization.